IMPLEMENTASI SCIENTIFIC APPROACH PEMBELAJARAN IPA DI MI SE KABUPATEN WAY KANAN - Nur Kholis (LP2M STIT Al-Hikmah Way Kanan, 2020)
Abstract Issues raised in this study is the application of local content-based science teaching with a scientific approach. It is intended that teachers strengthen their ability in facilitating students to be trained to think scientific by combining local advantages that have significance for the development of the region in the future. This research was conducted in MI Mangunsari Kota Salatiga in grade III and IV students by using purposive sampling technique. The type of research is qualitative and ex post facto (explorative) that aims to describe the state / status of phenomena. Instruments used to obtain research data in the form of observation and interview. The conclusions of this research are: 1) implementation of scientific approach in local content-based science teaching in MI Mangunsari Kota Salatiga is running well; 2) The characteristic of a scientific approach in local content-based science teaching in MI Mangunsari is unique by applying qasidah songs integrated with the science learning materials; 3) Obstacles to the application of local content in science learning are still limited local content of materials used. Keywords: Scientific Approach, IPA